Pengaruh Kepemilikan Institusional terhadap Struktur Modal dan Nilai Perusahaan di Indonesia - Andriyani Surjadi; Irene Vania; Wijantini Wijantini; Retno Yuliati (Universitas Prasetiya Mulya, 2018)
This study aimed to investigate the influence of institutional ownership on firm value and capital structure, also the influence of capital structure on firm value. This study contributes as a confirmation of the prior studies’ findings. Capital structure is measured with long-term debt to equity and firm value is measured with Tobin’s Q. Sample for this study includes 160 manufacturing companies listed on Bursa Efek Indonesia (BEI) in 2006-2015. The regression model used is Pooled Ordinary Least Squares (OLS). The findings of this study indicate that institutional ownership positively influences firm value by practicing effective monitoring which reduces agency problem, consistent with Jafarinejad (2015) and Lins (2003). Institutional ownership negatively influences capital structure assessed through pecking order theory, caused by the decreased information gap between shareholder and management and the institutional ownership’s monitoring as a subtitute of debt and in line with Michaely and Vincent (2013) and Chaganti and Damanpour (1991). Capital structure positively influences firm value as debt has a controlling role in the company will reduce agency problem thus raising firm value, consistent with agency theory developed by Jensen and Meckling (1976). The result is consistent with Hasbi (2015) and Zeitun and Tian (2007). Keywords: Agency Theory, Capital, Structure, Firm Value, Institutional Ownership, Peck ing Order Theory https://doi.org/10.21632/saki.1.2.110-133